Um novo olhar sobre a metodologia do ensino da geografia no ensino médio - VIEIRA, Cely Ferreira (Universidade Federal do Oeste do Pará, 2024)
With the increasing changes occurring on the planet and in society, this article focuses on the importance of developing new methodologies and directing to a pedagogical practice that can cover the school context in high school. in the most proletarian era of globalization still encounters traditional methods in certain educandarios. in this sense it is fundamental that teachers begin to use in their innovative rnethods, and thus to become more attractive their activities through their students, since iii the technological era in which we are inserted, it is necessary te, rethink about the teaching practice. aiming at the necessity to create innovative situations with regard to teaching / learning methodologies, exploring the different types of language. a bibliographic research was carried out to serve as a theoretical basis for the proposed theme. it is intended to contribute to the discussion of geography teaching taking into account the reality of public education t the secondary level.